The Policy Formulation of Educational Funding in Yogyakarta Province - Nurhayati, Riana; Rohman, Arif; Hajaroh, Mami; Sholikhah , Ebni (KnE Social Sciences, 2019)
The quality of education is depends on input factors. Funding is one of input factors which still an obstacle faced by disadvantaged groups. The local government in decentralization era has responsibility to carry out education and its funding as an implication of regional autonomy. This study aims to analyze the policy formulation of education funding in Yogyakarta Province by case study method. Primary data was collected by interviews and document collection. We found that the policy formulation of education funding consists of problem formulation, identification of alternatives, and budgeting. Stakeholders used brainstorming methods to formulate problems and identification alternative. They found some problems which can be distinguished into; minimum service standard, child abuse, and education management. Whereas, budgeting is determined by conformation mechanism between requirement of the problem solving and the themes of regional development plans. So that, the problems identification and program preparation carried out democratically but the determination of budgeting were carried out by bureaucratic and top-down manner. Necessarily, formulating problem-based policy is more important than prioritizing plan with outdated problem. Then, democratic policy which organized as bottom level stakeholders participation take an important role because they closer and better know about society problem.